2019
DOI: 10.1371/journal.pone.0212565
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical modelling approach to assess multi pollutant effects in time-series studies

Abstract: When assessing the short-term effect of air pollution on health outcomes, it is common practice to consider one pollutant at a time, due to their high correlation. Multi pollutant methods have been recently proposed, mainly consisting of collapsing the different pollutants into air quality indexes or clustering the pollutants and then evaluating the effect of each cluster on the health outcome. A major drawback of such approaches is that it is not possible to evaluate the health impact of each pollutant. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…However, the single-pollutant approach has typically been used in previous studies due to issues related to correlations between pollutants and different levels of measurement error for different pollutants. 20 No associations were observed between occupational exposures to rubber dust, rubber fumes and N-Nitrosamines with premature mortality from asthma, urinary diseases, bronchitis, emphysema, liver disease, and diseases of the oesophagus, stomach and duodenum. Previous studies also found no excess risks of mortality from liver and urinary disease in the rubber industry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the single-pollutant approach has typically been used in previous studies due to issues related to correlations between pollutants and different levels of measurement error for different pollutants. 20 No associations were observed between occupational exposures to rubber dust, rubber fumes and N-Nitrosamines with premature mortality from asthma, urinary diseases, bronchitis, emphysema, liver disease, and diseases of the oesophagus, stomach and duodenum. Previous studies also found no excess risks of mortality from liver and urinary disease in the rubber industry.…”
Section: Discussionmentioning
confidence: 99%
“…In multipollutant models, excess risks of dying from cerebrovascular, circulatory, digestive, respiratory diseases and IHD were only found for NSS exposure, but linear exposure–response associations were not observed. However, the single-pollutant approach has typically been used in previous studies due to issues related to correlations between pollutants and different levels of measurement error for different pollutants 20. No associations were observed between occupational exposures to rubber dust, rubber fumes and N-nitrosamines with premature mortality from asthma, urinary diseases, bronchitis, emphysema, liver disease and diseases of the oesophagus, stomach and duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the best pollutant is reported. In recent years, especially for air pollutants, hierarchical methods that model spatio-temporal processes and measurement noise were popular [ 34 , 35 ]. We plan to apply such models in the future to make our results more accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Dionisio et al (2016) fitting two-pollutant time-series models with additive and multiplicative error reported total effect attenuation up to 85% for NO 2 (close to our estimates for multiplicative error), indicating multi-pollutant model estimates are even more susceptible to ME [ 38 ]. Blangiardo et al (2019) also found, under a Bayesian framework, that NO 2 effects were considerably biased when error-prone concentrations were used [ 39 ]. However, they focused on collinearity in multi-pollutant models without assessing error structures/types.…”
Section: Discussionmentioning
confidence: 99%